Workload-indexed blood pressure response to a maximum exercise test among professional indoor athletes. (7th May 2020) - Bauer, Pascal; Kraushaar, Lutz; Dörr, Oliver; Nef, Holger; Hamm, Christian W; Most, Astrid
Abstract: Background: Exercise testing is performed regularly in professional athletes. However, the blood pressure response (BPR) to exercise is rarely investigated in this cohort, and normative upper thresholds are lacking. Recently, a workload-indexed BPR (increase in systolic blood pressure per increase in metabolic equivalent of task (SBP/MET slope)) was evaluated in a general population and was compared with mortality. We sought to evaluate the SBP/MET slope in professional athletes and compare it with performance. Design: This was a cross-sectional study. Methods: A total of 142 male professional indoor athletes (age 26 ± 5 years) were examined. Blood pressure was measured at rest and during a standardized, graded cycle ergometer test. We assessed the BPR during exercise, the workload, and the metabolic equivalent of task (MET). Athletes were divided into groups according to their SBP/MET slope quartiles (I <4.3; II 4.3–6.2; III >6.2–9; IV >9 mmHg/MET) and compared regarding systolic BP (sBP) and workload achieved. Results: Athletes in group I ( n = 42) had the lowest maximum sBP (180 ± 13 mmHg) but achieved the highest relative workload (4.2 ± 1 W/kg). With increasing SBP/MET slope, the maximum sBP increased (II ( n = 56): 195 ± 15 mmHg; III ( n = 44): 216 ± 16 mmHg) and the workload achieved decreased (II: 3.9 ± 0.7 W/kg; III: 3.3 ± 0.5 W/kg). The differences in sBP between these groups were significant ( p < 0.001). None of the athletes were assigned to group IV (>9 mmHg/MET). Conclusion: Athletes in the lowest SBP/MET slope quartile displayed the lowest maximum sBP but achieved a higher workload than athletes classified into the other SBP/MET slope groups. This simple, novel metric might help to distinguish a normal from an exaggerated BPR to exercise, to identify athletes at risk of developing hypertension.